A time like no other: Russian politics after the end of history - Sergei Prozorov (Danish Institute for International Studies (DIIS), 2006)
The paper ventures a reading of Russian postcommunist politics from the perspective of the messianic turn in continental political philosophy, specifically Giorgio Agamben's conception of the `end of history'. Taking its point of departure from a retrospective construction in the Russian political discourse of the 1990s as a period of `timelessness', the paper argues that postcommunism may indeed be viewed as a paradoxical `time out of time', a rupture in the ordinary temporality that entirely dispenses with the teleological horizon of politics. While the problematic of the `end of history' has been popularised by Francis Fukuyama's liberal recasting of Kojeve's reading of Hegel, the Russian experience is entirely contrary to this complacent and self-gratifying account of the triumph of liberalism but rather accords with Agamben's understanding of the end of history as the deactivation of the teleological dimension of politics as such. The paper concludes with outlining the implications of this reading of Russian postcommunism for understanding the present conjuncture of Russian politics, particularly the difference between the Yeltsin and the Putin presidencies.
Keywords: 330